Unpacking self-management in colorectal cancer with stoma patients: a comprehensive concept analysis - Ratna Aryani; Toar JM Lalisang; Debie Dahlia; Evi Martha; Yeni Rustina; Hening Pujasari (Palliative Medicine in Practice)
BACKGROUND: Self-management has become an important issue discussed by healthcare providers and healthcare systems due to the increase in chronic disease cases, the high cost of chronic disease conditions, and the limited time of health workers. This study aimed to comprehensively and specifically explore and clarify self-management in stoma patients with colorectal cancer. Identifying the key attributes, antecedents, and consequences of self-management in this population will increase understanding in creating strategies and providing more appropriate nursing interventions in improving patient’s quality of life. METHODS: This study used Walker and Avant’s concept analysis technique to investigate the concept of self-management in colorectal cancer stoma patients, which involves an eight-step process. Thematic analysis identified key attributes, antecedents, and consequences of self-management based on a review of relevant literature and existing theoretical frameworks. RESULTS: Self-management is described as the ability of a person with a chronic disease condition to manage symptoms, treatments, physical and psychosocial impact, and lifestyle changes that affect his life. Outcomes can be achieved if patients have personal/lifestyle characteristics, health status, resources, environmental characteristics, and health care system. The outcomes include improved self-care, self-efficacy, ability to change stoma bag, quality of life, self-management behavior, self-care attitude, self‑care behavior, and stoma proficiency. CONCLUSIONS: Key attributes identified, such as managing skills, goal achievement, caring, and life satisfaction, highlight the need for nurses to equip patients with essential self-care knowledge and skills. By doing so, healthcare providers can enhance patient autonomy, reduce healthcare costs, and foster better health outcomes.